1998
DOI: 10.1562/0031-8655(1998)067<0433:ubimti>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Irradiation Modulates the Immune System of Fish (Rutilus rutilus, Cyprinidae). I. Phagocytes

Abstract: Roach (Rutilus rutilus) were irradiated with a single dose of ultraviolet B (UVB) radiation (0.4 J/cm2) in order to study the effects of UVB on the nonspecific immune defense mechanisms of fish. Neutrophils and macrophages were isolated from the head kidney of fish on days 1-14 postirradiation. Both random and directed migration of neutrophils, studied by migration under agarose assay, were suppressed on day 1 after UVB irradiation. The respiratory burst of phorbol 12-myristate 13-acetate-stimulated neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…Phorbol 12-myristate 13-acetate (PMA)-stimulated respiratory burst by phagocytes was determined by the luminolenhanced chemiluminescence (CL) method [2,19]. The CL produced by blood and head kidney leucocytes was monitored with a microplate luminometer (Victor 2 Ô, 1420 Multilabel Counter, Wallac, Turku, Finland) in a 200 ml reaction volume at 25 C. Cells (2.5 Â 10 5 head kidney leucocytes, or 5 Â 10 5 blood leucocytes) or whole blood (5 ml) was suspended in incubation medium, and luminol was added to the wells.…”
Section: Respiratory Burst By Phagocytesmentioning
confidence: 99%
“…Phorbol 12-myristate 13-acetate (PMA)-stimulated respiratory burst by phagocytes was determined by the luminolenhanced chemiluminescence (CL) method [2,19]. The CL produced by blood and head kidney leucocytes was monitored with a microplate luminometer (Victor 2 Ô, 1420 Multilabel Counter, Wallac, Turku, Finland) in a 200 ml reaction volume at 25 C. Cells (2.5 Â 10 5 head kidney leucocytes, or 5 Â 10 5 blood leucocytes) or whole blood (5 ml) was suspended in incubation medium, and luminol was added to the wells.…”
Section: Respiratory Burst By Phagocytesmentioning
confidence: 99%
“…Negative effects of UVB and gamma irradiation on the immune system of fish (Salo et al, 1998;Markkula et al, 2006;Engel, 1967;Gwozdzinski, 1991;Cassidy et al, 2007;Anbumani and Mohankumar, 2012) have been reported. In another study by Almasiova et al (2012), deterioration in renal interstitial tissue and hematopoietic tissue, which plays an important role in the formation of erythrocytes and leukocytes and the number of blood vessels, was observed in guppy fish exposed to 20 Gy gamma radiation.…”
Section: Discussionmentioning
confidence: 99%
“…After collection, the organ was placed in an Eppendorf tube with Hank's Na + and Ca 2+ free balanced salt solution and a drop of heparin and homogenized through a nylon net (mesh size, 80 mesh, i.e. wires per inch, about 300 μm) (Salo et al 1998). The homogenate was layered on a two-step Percoll gradient (Pharmacia LKB Biotechnology, Uppsala, Sweden).…”
Section: Immunological Analyses and Testosterone Determinationsmentioning
confidence: 99%
“…In fish, phagocytes are the most important component of the cellmediated immune system (Finco-Kent and Thune 1987;Secombes and Fletcher 1992), and the ability of these cells to produce oxidative anions has been used to describe their ability to kill pathogens (Collazos et al 1995;Salo et al 1998). In this study, we measured this ability as chemiluminescence of blood (1) and chemiluminescence of head kidney phagocytes (2).…”
Section: Introductionmentioning
confidence: 99%